REJESTRACJA I ZMIANA NAZWISKA - Łakoma, Sylwia (Wydział Prawa i Administracji UAM, 2008)
A surname - apart from a name - is a very important element when it comes to the confirmation of the identity of a particular person. It is necessary for official determination o f a person in order to distinguish him/her in social contacts with other people. The surname is a legal category. It is a personal interest protected by law. Registration of the surname and its use is a person’s legal right as well as a duty. This, in turn, implies both, the stability and legal protection the registered name, and the existence of a legal possibility to change the surname, i f justifiable. Registered name is a notion present in public and private law. An initially given surname is related to the birth and indicates the person’s descent. Legal registration o f a name involves drawing up the birth certificate o f a newly bom child. This may take the form o f primary or secondary proceedings. However, the change of the originally registered name, regardless of the reasons, moves the registration o f a new name into the category of secondary proceedings. A registered name usually remains unchanged until marriage, which is compliant with art. 25 § 2 the Polish Family and Guardianship Code. Other changes of surname pursuant to the aforementioned Code are connected, among others, with child adoption. Apart from the possibility of the change of surname based on the Polish family law, there are regulations providing for the possibility o f an administrative change of surname - “because o f serious reasons”. These issues are regulated by the Change of Surname Act which defines the rules and the process of the change of surnames (and names). In principle, the change o f surname is carried out at the request and upon on application of the person bearing that name and follows the declaration of that person’s will. An exception to the principle applies to minors, where an application for a change of name is filed by their statutory agents acting on their behalf (sometimes with the minor’s consent).
REGISTRATION AND CHANGE OF SURNAME